Comparative Evaluation of Toggle Rod Technique and Toggle Pin Technique for the Repair of Coxofemoral Luxation in Dogs - Mahadev Jekinakatti, Kanteshkumar; Dasalukunte Ramaiah, Manjunatha; Dhoopadahalli, Vilas; Ramappa Balappanavar, Basavaraj; Mahadev Jekinakatti, Sannathkumar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The clinical study was conducted to evaluate the toggle rod technique and toggle pin technique for the repair of coxofemoral luxation in ten clinical cases of dogs of either sex, aged 1 to 8 years, and of different breeds. Dogs were brought with a history of limping and non weight bearing lameness mostly following automobile accidents. Orthopaedic and radiographic examination confirmed coxofemoral luxation in all dogs. Under inhalant anaesthesia luxation was stabilised with toggle rod technique in three cases and toggle pin technique in seven cases via craniodorsal approach. Post-operatively an Ehmer’s sling and pelvic bandage was applied and limited activity with short leash walk was advised. Intra-operative complications were not observed in any of the operative techniques. Post-operative radiographic evaluation revealed proper alignment and anatomical configuration of coxofemoral joint in both, toggle rod and toggle pin techniques. All dogs with toggle pin technique showed excellent weight bearing and limb usage on 30th post-operative day onwards. Toggle rod technique had reluxation as a complication. All the dogs with toggle pin technique recovered uneventfully and reluxation in toggle rod technique was treated with femoral head and neck excision. In conclusion clinical results were excellent with toggle pin technique than toggle rod technique in dogs for the repair of coxofemoral luxations.
Keywords: Coxofemoral luxation; Craniodorsal; Dog; Reluxation; Toggle pin; Toggle rod